Tabu Search for Locating-Routing in the Goods Delivery and Waste Pickup in Trujillo-Peru - Lujan Segura, Edwar (2022)
The purpose of this work concerns about Metaheuristics Tabu Search (TS). It deals with optimizing logistic and environmental cost by delivery of goods and waste pickup generated in Trujillo-Peru. The problem arises in two levels, which are focused on locating facilities and creating routes to minimize expenses and produce the lowest amount of CO2. The TS was implemented in the C programming language and assessed for individual instances, it consists on real data of the geographical coordinates of the providers, facilities and customers of the city, simulated data of orders, collections and cost of facilities, among others. The results for different instances show that satisfactory solutions were found in acceptable time, achieving the location of facilities and the creation of routes with the least possible cost and the least amount of pollution. This work may be useful for other cities in Peru or other countries with similar problem.